La circularidad entre Antropología y Metafísica en la encíclica «Fides et ratio» - García Cuadrado, José Angel (Scripta theologica, 2023)
In the bibliography about Fides et ratio, have been highlighted the defense of metaphysics and the idea of circularity between philosophy and theology. Here we hypothesize that the relationship between anthropology and metaphysics is analogous to the circularity between philosophy and theology. This is the path for the renewal of metaphysics proposed by John Paul II. First of all, I will present the conception of the encyclical on metaphysics and anthropology. Then, I will describe the concept of «circularity», to go on to apply it to the relationship between metaphysics and anthropology. Finally, I will show the relevance of this proposal for a Christian humanism.